Research priorities to support the development of integrated national strategies to control skin-neglected tropical diseases. (21st September 2022) - Simpson, Hope; Mengiste, Asrat; Mbonigaba, Jean Bosco; Kollie, Karsor; Nganda, Motto; Dean, Laura; Argaw, Daniel; Davey, Gail; Semrau, Maya
Abstract: Background: Skin-presenting neglected tropical diseases (skin-NTDs) impose large burdens on affected people, families and communities. The NTD Roadmap 2021–2030 presents a strategic plan to guide collaborative, multisectoral action to overcome these burdens, defining targets to control, eliminate and/or eradicate skin-NTDs by 2030. One of its targets is for 40 countries to adopt integrated skin-NTD strategies. Despite this high-level support for integration, only four countries were implementing integrated skin-NTD strategies in 2020. Methods: We hosted workshops at the 2021 annual meeting of the Coalition for Operational Research on NTDs, to discuss the operationalisation of Roadmap goals into national strategies and interventions for skin-NTD control. Speakers included NTD Programme Managers from NTD-endemic countries, technical experts and researchers of different aspects of skin-NTDs. Results: Challenges include community perceptions of interventions, demonstrating the cost-effectiveness of integrated care, availability and accessibility of community-based and primary healthcare services, the quality of data on skin-NTD morbidity and changes to operational structures required for integration. Research priorities included the identification of optimal case detection platforms, evaluation of integrated care, understanding the impacts of integration on community members and community health staff and development of point-of-care diagnostics. Conclusions: The operational research priorities are intended to support the scale-up of integrated skin-NTDs programmes.